Successful treatment of locally advanced lung cancer using late concurrent chemoradiation therapy administered after immune checkpoint inhibitor plus platinum chemotherapy - Taichi Matsubara (Wiley, 2021)
Abstract Concurrent chemoradiation therapy (CRT) is the standard of care for patients with unresectable stage II/III lung cancer. However, systemic chemotherapy is required for patients who are ineligible for radical radiation therapy. There is little evidence to date for the safety and efficacy of CRT administered after treatment with immune checkpoint inhibitors (ICIs). The cases reported here had inoperable stage III lung cancer (non‐small cell lung cancer and small cell lung cancer) and were ineligible for radical radiation therapy. They were administered ICIs plus chemotherapy and subsequently underwent late concurrent CRT. Because of the remarkable tumor shrinkage achieved by the ICIs plus chemotherapy, adverse events of CRT were tolerable. They were alive without tumor progression as of this report, over 1 year after CRT was terminated. CRT is administered with curative intent, while the intent of immunochemotherapy is palliative. Late concurrent CRT after immunochemotherapy is probably effective and tolerable. After treatment with systemic chemotherapy in patients judged ineligible for radical radiation therapy, radiation therapy should be reconsidered because of its importance once tumor shrinkage has been achieved.